Strategic target setting in the heptathlon - Dinnie, A.; O`Donoghue, P. (Journal of Sports Analytics, 2020)
The purpose of this study was to examine scoring within the women`s Heptathlon to identify areas of performance where athletes could most improve their points total and propose an approach to target setting. Performance data were gathered from publically available sources for 409 performances of 155 heptathletes at 19 international championships between 2004 and 2017 inclusive. Based upon the interquartile ranges, the largest spread of points were seen for the High Jump and Javelin. Year to year improvement was analysed using the 186 pairs of performances by the same athletes in consecutive calendar years. This showed that the disciplines with the most scope for improvements were the Long Jump, High Jump and Javelin. The proposed target setting approach can be used to identify which disciplines an athlete should focus on to maximise improvement in their total points and to estimate the probability of the athlete exceeding the target that has been set. The approach should be used in conjunction with knowledge of the wider context of the athlete`s recent heptathlon performances.